2020
DOI: 10.1007/s10198-020-01200-0
|View full text |Cite
|
Sign up to set email alerts
|

The excess economic burden of mental disorders: findings from a cross-sectional prevalence survey in Austria

Abstract: Information about the scope of mental disorders (MDs), resource use patterns in health and social care sectors and economic cost is crucial for adequate mental healthcare planning. This study provides the first representative estimates about the overall utilisation of resources by people with MDs and the excess healthcare and productivity loss costs associated with MDs in Austria. Data were collected in a cross-sectional survey conducted on a representative sample ( n = 1008) between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
1
14
1
4
Order By: Relevance
“…Recent analysis from a convenience sample survey in Australia looking at time spent caring by family carers for a range of mental health conditions had similar findings to this study; they estimate that primary carers provide on average approximately 36 h of care per week, with 38% caring for 40 or more hours per week [ 3 , 21 , 22 ]. In contrast, a cross-sectional survey in Austria reported very low weekly hours of care of only 2.82 h per week, but this survey only interviewed people living with mental health conditions, rather than their carers [ 36 ]. In the Basque country, in Spain, a convenience sampling survey of more than 200 carers supporting people with eating disorders, depression and schizophrenia, respectively, reported that 44%, 68% and 33% of carers were in contact with the person they support for more than 35 h per week [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis from a convenience sample survey in Australia looking at time spent caring by family carers for a range of mental health conditions had similar findings to this study; they estimate that primary carers provide on average approximately 36 h of care per week, with 38% caring for 40 or more hours per week [ 3 , 21 , 22 ]. In contrast, a cross-sectional survey in Austria reported very low weekly hours of care of only 2.82 h per week, but this survey only interviewed people living with mental health conditions, rather than their carers [ 36 ]. In the Basque country, in Spain, a convenience sampling survey of more than 200 carers supporting people with eating disorders, depression and schizophrenia, respectively, reported that 44%, 68% and 33% of carers were in contact with the person they support for more than 35 h per week [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even minor changes in definitions may cause considerable variation in the estimation of disease prevalence and service utilization [4,5]. Another factor is that although the economic burden of mental diseases in regards to costs is thought to be massive [6], resulting in doubled total costs for persons with mental diseases compared to those without [7], calculating exact costs is complicated [8,9]. This is particularly the case if health care provision and funding are both fragmented, such as in Austria [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the lack of available data and valuation methods [20]. At the same time, these inter-sectoral costs were found to contribute a considerable proportion to the total costs of mental diseases [7,15,21,22]. With economic evaluations being increasingly used as a base for decision making in healthcare, a comprehensive reflection of the societal costs associated with a disease is also vital in this context and has been already recommended in national health economics guidelines in the Netherlands and Spain [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Similar spill-over costs are also relevant for persons providing informal care to patients [ 19 ]. As health economic evaluations are among the essential groundwork for evidence-informed policy decision making, sensible consideration of a societal perspective is important and has been taken up in recent cost of illness studies [ 20 , 21 ]. However, the quality of intersectoral, i.e., sector overarching, health economic analyses, and the resulting empirical evidence depends critically on the compatibility of the methods used in the cost assessment in the different sectors, in particular with regard to quantifying costs.…”
Section: Introductionmentioning
confidence: 99%